THE PERCEIVED IMPACT OF MICRO AND MACRO CONTEXTUAL FACTORS ON THE TEACHERS’ PROFESSIONAL IDENTITY DEVELOPMENT IN THE INDONESIAN RURAL AREA - Gregoriana Nobilio Pasia Janu; Concilianus Laos Mbato (PROJECT (Professional Journal of English Education), 2023)
The primary goal of this paper is to understand the extent to which the significance of macro and micro contextual factors influence rural teachers' professional identity development in Manggarai, NTT. Qualitative methods were employed, involving four rural teachers who shared their perspectives through an open-ended online questionnaire. The findings revealed a positive attitude towards factors such as effective communication with students and colleagues, recognition, and access to training opportunities for professional support. Unstructured interviews were conducted to delve deeper into how these factors influenced the teachers' professional identity construction and development in practice. The results indicated that, apart from the national examination due to educational reforms, the macro-contextual factors played a supportive role in the cognitive dimension, emphasizing the teachers' desire for professional growth. Despite expressing dissatisfaction with administrative demands and supervision, the participants valued the positive experiences derived from both factors. The study's focus on both micro and macro contextual factors may limit the depth of understanding regarding their specific impacts on professional identity, requiring future research to explore individual factors in greater detail. Additionally, the use of senior teachers in rural areas as participants may restrict generalizability, suggesting the need for diverse participants to capture variations in perceptions and practices across different settings.